2004
DOI: 10.1192/pb.28.12.444
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry as a career choice compared with other specialties: A survey of medical students

Abstract: Aims and MethodThe aim of this study was to determine the attitudes of medical students in the UK towards different specialties as career options and to ascertain the position of psychiatry among these specialties. Students belonging to a London medical school completed a questionnaire.ResultsAmong the 301 students who completed the survey, psychiatry was the least popular clinical specialty. The study revealed that the students had a number of misconceptions about psychiatry. A family history of mental illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 10 publications
9
67
1
Order By: Relevance
“…Positive placement experiences have been shown to improve students' attitudes to psychiatry (Eagles et al 2007) and positive attitudes of teachers at medical school can be influential in helping students choose psychiatry as a career (McParland et al 2003;Dein et al 2007). Despite these positive influences, psychiatry is often viewed as a lower status specialty among both students and professionals (Hunt et al 1996;Eagles et al 2007) and is seen by students as an unattractive career choice about which they often hold misconceptions (Rajagopal 2004). This was a single medical school survey as are most recent surveys of medical student attitudes to psychiatry attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Positive placement experiences have been shown to improve students' attitudes to psychiatry (Eagles et al 2007) and positive attitudes of teachers at medical school can be influential in helping students choose psychiatry as a career (McParland et al 2003;Dein et al 2007). Despite these positive influences, psychiatry is often viewed as a lower status specialty among both students and professionals (Hunt et al 1996;Eagles et al 2007) and is seen by students as an unattractive career choice about which they often hold misconceptions (Rajagopal 2004). This was a single medical school survey as are most recent surveys of medical student attitudes to psychiatry attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The longstanding factors that have dissuaded medical students and newly qualified doctors from pursuing a career in psychiatry have already been well described in literature in the USA 3,[5][6][7][8][9][10] and there is a growing evidence base in the UK. 1,[11][12][13] Although individual factors have been identified, the constellation of all the key issues in the UK has not yet been addressed collectively.…”
mentioning
confidence: 99%
“…Goldacre et al (2004) found that only 4.3% of all respondents in the first year after their graduation signified that psychiatry was their first choice of long-term career, and there had been very little change between 1974 and 2000. Psychiatry was the least popular clinical specialty in a London medical school (Rajagopal et al, 2004).…”
mentioning
confidence: 99%